Late Middle Pleistocene hominin teeth from Tongzi, southern China. Issue 130 (May 2019) - Xing, Song; Martinón-Torres, María; Bermúdez de Castro, José María
Abstract: In 1972 and 1983, four hominin teeth were recovered from Yanhui Cave, Tongzi, southern China and assigned to later Homo erectus or archaic Homo sapiens . The teeth can be dated to approximately 172, 000–240, 000 years before present. Here, in addition to the standard morphological comparisons, we reevaluate the morphology of the hominin teeth using geometric morphometric analyses and micro-computed tomography (micro-CT) scans. The Tongzi teeth were primarily compared to hominins from the same chronological period (late Middle Pleistocene) and/or the same geographic area (East Asia), although a wide range of hominins were included in the comparative sample. This study reveals that the Tongzi teeth do not fit the morphological pattern of classic H. erectus, and expands our understanding of the morphological diversity of the Asian Middle Pleistocene hominins. Overall, our results point to the existence of more than one paleodeme in East Asia during this period: one that can be taxonomically classified as H. erectus sensu stricto (represented by fossils such as Zhoukoudian, Hexian, and Yiyuan) and a second that is characterized by the expression of derived traits more commonly found in later Homo (such as the crown symmetry, lingual reduction, and simplified EDJ surface of the third premolar). More fossil and genetic findings will help assess the taxonomy of the "non- erectus " Asian Middle Pleistocene populations, like the Tongzi hominins.